2019
DOI: 10.1136/bmjopen-2017-017995
|View full text |Cite
|
Sign up to set email alerts
|

Impact of bacterial probiotics on obesity, diabetes and non-alcoholic fatty liver disease related variables: a systematic review and meta-analysis of randomised controlled trials

Abstract: ObjectiveTo systematically review the effect of oral intake of bacterial probiotics on 15 variables related to obesity, diabetes and non-alcoholic fatty liver disease.DesignSystematic review and meta-analysis.Data sourcesMedline, EMBASE and COCHRANE from 1990 to June 2018.Eligibility criteriaRandomised controlled trials (≥14 days) excluding hypercholesterolaemia, alcoholic liver disease, polycystic ovary syndrome and children <3 years.ResultsOne hundred and five articles met inclusion criteria, representing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
190
3
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 233 publications
(211 citation statements)
references
References 133 publications
(147 reference statements)
10
190
3
8
Order By: Relevance
“…Our study is one of the first to report the impact of a multi-strain probiotic on weight loss in response to 6-months supplementation in a cohort of healthy, overweight and obese, free-living (no dietary or lifestyle restrictions) subjects. More weight loss occurred in the overweight subjects (SG1a) compared with the obese (SG1b) receiving probiotics agreeing with the meta-analysis findings of Koutnikova and colleagues of greater weight loss in probiotic supplemented overweight participants than obese 10 . No weight loss was observed at the midpoint (3 months) of our study as has been shown in a number of short-term probiotic studies in free-living overweight/ obese subjects [18][19][20] .…”
Section: Discussionsupporting
confidence: 86%
“…Our study is one of the first to report the impact of a multi-strain probiotic on weight loss in response to 6-months supplementation in a cohort of healthy, overweight and obese, free-living (no dietary or lifestyle restrictions) subjects. More weight loss occurred in the overweight subjects (SG1a) compared with the obese (SG1b) receiving probiotics agreeing with the meta-analysis findings of Koutnikova and colleagues of greater weight loss in probiotic supplemented overweight participants than obese 10 . No weight loss was observed at the midpoint (3 months) of our study as has been shown in a number of short-term probiotic studies in free-living overweight/ obese subjects [18][19][20] .…”
Section: Discussionsupporting
confidence: 86%
“…This finding is specific to probiotics among other supplements reported in the survey, and the effect persists in a sample composed of dogs without major reported health issues. This relationship is supported by work that shows significant differences in the gut microbiota of normal and obese dogs (23), as well as recent reviews and meta-analyses of experimental and clinical trials of probiotic supplementation in different species (24)(25)(26). However, to the best of our knowledge this is the first large cross-sectional demographic study that has specifically identified probiotic supplementation as a potential protective factor with regard to overweightness and obesity.…”
Section: Discussionmentioning
confidence: 63%
“…[129] A meta-analysis demonstrated that subjects with NAFLD had a consistently lower body mass index (BMI) and fat content after supplementation with Bifidobacterium. [130] Another randomized clinical trial suggested that the VSL#3 probiotic plays a beneficial role in ameliorating childhood obesity and NASH, decreasing BMI, and increasing the GLP-1 level. [131] This liver protective effect was also demonstrated in several rodent experiments.…”
Section: Probiotics Prebiotics and Symbioticsmentioning
confidence: 99%